Cutaneous Vasculitis and Digital Ischaemia Caused by Heterozygous Gain-of-Function Mutation in C3 - Omoyinmi, Ebun; Mohamoud, Iman; Gilmour, Kimberly; Brogan, Paul A.; Eleftheriou, Despina (Frontiers in Immunology, 2018)
It is now increasingly recognized that some monogenic autoinflammatory diseases and immunodeficiencies cause vasculitis, although genetic causes of vasculitis are extremely rare. We describe a child of non-consanguineous parents who presented with cutaneous vasculitis, digital ischaemia and hypocomplementaemia. A heterozygous p.R1042G gain-of-function mutation (GOF) in the complement component C3 gene was identified as the cause, resulting in secondary C3 consumption and complete absence of alternative complement pathway activity, decreased classical complement activity, and low levels of serum C3 with normal C4 levels. The same heterozygous mutation and immunological defects were also identified in another symptomatic sibling and his father. C3 deficiency due GOF C3 mutations is thus now added to the growing list of monogenic causes of vasculitis and should always be considered in vasculitis patients found to have persistently low levels of C3 with normal C4.